2022
DOI: 10.3390/en15062165
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Fiber Fracturing Fluid Controlling Pulverized Coal Transportation

Abstract: In view of the problems associated with coal powder production in the development of Coalbed Methane (CBM), a fiber fracturing fluid technology is proposed to control pulverized coal production. Based on a force analysis of coal powder in the fracture and the microstructure of fiber-proppant, a critical intercepted particle size model of coal powder is established. This model is primarily related to fiber properties, proppant particle size and flow rate. To verify this, an FCES-100 device (Nantong Yichuang Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In high-viscosity fracturing fluid, fiber and proppant form a fiber-proppant cluster to improve the delivery efficiency of proppant and increase the conductivity of proppant. The network structure formed by the fiber can maintain the stability of the proppant and prevent the backflow of the proppant [14][15][16]. However, this technology still has certain limitations, and the fracturing fluid still needs to be highly viscous [17].…”
Section: Introductionmentioning
confidence: 99%
“…In high-viscosity fracturing fluid, fiber and proppant form a fiber-proppant cluster to improve the delivery efficiency of proppant and increase the conductivity of proppant. The network structure formed by the fiber can maintain the stability of the proppant and prevent the backflow of the proppant [14][15][16]. However, this technology still has certain limitations, and the fracturing fluid still needs to be highly viscous [17].…”
Section: Introductionmentioning
confidence: 99%
“…A series of laboratory evaluations were designed to quantify the effectiveness of fibers on proppant flowback control. Wang and Zhao 21 proposed to control pulverized coal production by a fiber fracturing fluid technology. Based on a force analysis of coal powder in the fracture and the microstructure of the fiber-proppant, a critical intercepted particle size model of coal powder is established.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reasonable prevention and control measures of pulverized coals are very important to achieve good permeability and fracture conductivity of coal seams. A large number of experiments on pulverized coal prevention and control have been conducted in the lab and by field study [5][6][7]. It is found that the surface wetting properties of pulverized coal can be greatly changed by the introduction of surfactants [8][9][10][11][12][13][14][15][16][17][18] or changing its particle size and other variables, providing a theoretical basis for pulverized coal control [19][20][21].…”
Section: Introductionmentioning
confidence: 99%